1986
DOI: 10.1152/ajpregu.1986.250.5.r823
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure by doubly labeled water: validation in humans and proposed calculation

Abstract: To further validate the doubly labeled water method for measurement of CO2 production and energy expenditure in humans, we compared it with near-continuous respiratory gas exchange in nine healthy young adult males. Subjects were housed in a respiratory chamber for 4 days. Each received 2H2(18)O at either a low (n = 6) or a moderate (n = 3) isotope dose. Low and moderate doses produced initial 2H enrichments of 5 and 10 X 10(-3) atom percent excess, respectively, and initial 18O enrichments of 2 and 2.5 X 10(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
516
2
5

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(534 citation statements)
references
References 23 publications
11
516
2
5
Order By: Relevance
“…where TBW is the total body water, and we assumed that isotope fractionation applied to both breath and transdermal water using equation (A6) from Schoeller et al (11) with the revised dilution space constant of Racette et al (12) . Calculation of TEE DLW (kJ/d) was performed using a modification of Weir's formula based on the r CO2 and mean food quotient of the subjects in the study (13,14) .…”
Section: Doubly Labelled Water Methodsmentioning
confidence: 99%
“…where TBW is the total body water, and we assumed that isotope fractionation applied to both breath and transdermal water using equation (A6) from Schoeller et al (11) with the revised dilution space constant of Racette et al (12) . Calculation of TEE DLW (kJ/d) was performed using a modification of Weir's formula based on the r CO2 and mean food quotient of the subjects in the study (13,14) .…”
Section: Doubly Labelled Water Methodsmentioning
confidence: 99%
“…The results on humans also showed that one general model (Eq. A6 derived by Schoeller et al 1986) is applicable at all stages. In contrast to the model employed by us on the Japanese Quail, Schoeller et al's (1986) Eq.…”
Section: Application Of the Dlw Methods During Growth And Adulthoodmentioning
confidence: 99%
“…A Europa Scienti®c Geo 20 ± 20 (Europa, Crewe, Cheshire, UK) isotope ratio mass spectrometer, which was calibrated against Vienna Standard Mean Ocean Water (V-SMOW) and International Atomic Energy Agency (IAEA) enriched standards 302A and 302B, was used to measure the 2 H 2 O concentrations in the batch doses and saliva samples (Dighton et al, 1997). The isotope dilution space was calculated in accordance with the recommendations of Schoeller et al (1986), who advocate a 4% correction factor for the exchange of deuterium with nonaqueous hydrogen. Our latest reliability and precision data for two TBW trials on alternate days (n 10) yielded an ICC of 0.998 and a TEM of 0.28 kg.…”
Section: Total Body Water (Tbw)mentioning
confidence: 99%